A study on English vocabulary learning strategies used by the first year students at Hai Phong Community College - Đỗ, Thị Kim Oanh (University of Languages and International Studies, 2017)
This paper reports on the learning of English vocabulary by college students at Hai Phong Community College. The purpose of this study was twofold: find out the students’ awareness of the important of vocabulary learning and what strategies are commonly used.